G284 Kawasaki disease bpsu survey in great britain and ireland. (27th April 2015) - Tulloh, RMR; Mayon-White, R; Craggs, PM; Shingadia, D; Michie, C; Harnden, A; Franklin, O; Ramanan, A; Tizard, EJ; Connolly, GM; Gargh, K; Davidson, S; et al.
Abstract : Introduction: Kawasaki disease (KD) is the commonest cause of acquired heart disease in the western world. We report here on the preliminary data for the first year of a 2-year national survey in Great Britain and Northern Ireland. Methods: Using standard BPSU methodology, children with Complete KD (for the first year) presenting from January 1 st to December 31 st 2013 were studied with their treatments and complications. The steering committee reviewed cases that were unclear or incomplete. Results: Excluding incomplete KD and incomplete data sets, there were 180 with complete KD (15/month). Peak presentation was in March, boy:girl ratio was 1.8 and 69% were 1 to 4 years old. The highest incidence was in children under 5 years especially in London and East Anglia (5.6 / 100, 000) and lowest in the Midlands (2.8/100, 000). Highest incidence was in Chinese (21.9/100, 000), Black African and Caribbean (14.5/100, 000) and Mixed ethnicity (15.3/100, 000). 81% saw a GP at median 2 days after fever commencement and admission was median (range) of 2 (0–27) days later. Fever duration was 6 (1–28) days. 97% had rash, usually at the start of fever, which was on the trunk or widespread in 89% and was macular in 75%. Bilateral non-purulent conjunctivitis (91%) occurred at 4 (0–27) days and mucositis (97%) at 5 (0–27) days. Periphery involvement was up to 32 days in 156 (86%). Lymphadenopathy was least common (65%) often after 5 days. The BCG scar was inflamed in 11. CRP ranged from 1–501 mg/l, albumin from 17–45g/l, lowest platelet counts were below 150 × 10^9/l in 14. 31 (22%) had dilated coronary arteries, 9 had pericardial effusion and 12 had ECG abnormalities. Intravenous immunoglobulin (2g/kg) given within 7 days to 95%, but not to 9 complete cases (delayed diagnosis). Second dose was given to 13 children. High dose aspirin (30–50mg/kg) followed by low dose aspirin was given to 92%. 19 had sequelae, 15 with persistence of coronary artery dilation, with no deaths. Conclusions: These preliminary results show a high incidence of coronary artery disease with the old guideline for KD and give new data on seasonality, ethnicity and correlation with clinical symptoms.